ACTUAL QUESTIONS THE USE OF GIS AND REMOTE SENSING IN GEOARCHEOLOGY - E. P. Krupochkin (InterCarto. InterGIS, 2014)
The article presents some relevant aspects of GIS and remote sensing data in the decision -theoretic methodological problems of geoarhaeology. The author has developed a flow chart which shows the key areas of aerospace information in mass geoarchaeological research. The main emphasis is on two factors – indicator interpretive properties artifacts which appear in the photographs; potential integrated use of remote sensing data in GIS for developed geoarhaeology. No less important result is presented conceptual model geoarchaeological GIS. Its purpose is not only to provide cartographic specialists archaeological information. The main condition for the development and implementation of its established on the basis of GIS products is extensive information and analytical capabilities. Such opportunities may occur in solving mathematical-cartographic modeling at the junction of industries such as archeology, geography, mathematics , geoinformatics , cartography , etc.